A prospective study of a protocol that reduces readmission after liver transplantation. Issue 6 (June 2016) - Russo, Mark W.; Levi, David M.; Pierce, Ruth; Casingal, Vincent; Eskind, Lon; deLemos, Andrew; Schmeltzer, Paul A.; Zamor, Philippe J.
Abstract : Health care has shifted to placing priority on quality and value instead of volume. Liver transplantation uses substantial resources and is associated with high readmission rates. Our goal was to determine if a protocol designed to reduce readmission after liver transplant was effective. We conducted a prospective study of a protocol designed to reduce readmission rates after liver transplantation by expanding outpatient services and alternatives to readmission. The 30‐day readmission rate 1 year after implementing the protocol was compared to the 30‐day rate for 2 years prior to implementation. Multivariate analysis was used to control for potential confounding factors. Over the study period, 167 adult primary liver transplants were performed with a mean biological Model for End‐Stage Liver Disease score of 21 ± 8. Fifty‐seven (34%) patients were readmitted. The most common reason for readmission was biliary complications (n = 13). The 30‐day readmission rate decreased from 40% before implementing the protocol to 20% after implementation ( P  = 0.02). In multivariate analysis, the protocol remained associated with readmission (odds ratio, 0.39; 95% confidence interval, 0.16‐0.92; P  = 0.03). The mean length of stay after transplant was 13 ± 12 days preprotocol and 9 ± 5 days postprotocol ( P  = 0.09). Alternatives to readmission, including hospital lodging and observation status, were main factors in reducing readmission rates. If the most recent definitions of inpatient admission and observation status were applied over the entire study period, then the readmission rates preprotocol and postprotocol were 31% and 20% indicating that the revised definition of observation status accounted for 45% of the reduction in the readmission rate. Readmission after liver transplantation can be reduced without increasing length of stay by implementing a specifically designed protocol that expands outpatient services and alternatives to inpatient admission. Liver Transplantation 22 765–772 2016 AASLD .